Gravitational waves: A statistical autopsy of a black hole merger. Issue 2 (April 2016) - Meyer, Renate; Christensen, Nelson
Abstract : Renate Meyer and Nelson Christensen explain how statistics and statisticians helped unravel a story 1 billion years in the making Abstract : Renate Meyer andNelson Christensen explain how statistics and statisticians helped unravel a story 1 billion years in the making